The Single‐Cell Landscape of Intratumoral Heterogeneity and The Immunosuppressive Microenvironment in Liver and Brain Metastases of Breast Cancer. Issue 5 (18th December 2022) - Zou, Yutian; Ye, Feng; Kong, Yanan; Hu, Xiaoqian; Deng, Xinpei; Xie, Jindong; Song, Cailu; Ou, Xueqi; Wu, Song; Wu, Linyu; Xie, Yi; Tian, Wenwen; et al.
Abstract: Distant metastasis remains the major cause of morbidity for breast cancer. Individuals with liver or brain metastasis have an extremely poor prognosis and low response rates to anti‐PD‐1/L1 immune checkpoint therapy compared to those with metastasis at other sites. Therefore, it is urgent to investigate the underlying mechanism of anti‐PD‐1/L1 resistance and develop more effective immunotherapy strategies for these patients. Using single‐cell RNA sequencing, a high‐resolution map of the entire tumor ecosystem based on 44 473 cells from breast cancer liver and brain metastases is depicted. Identified by canonical markers and confirmed by multiplex immunofluorescent staining, the metastatic ecosystem features remarkable reprogramming of immunosuppressive cells such as FOXP3+ regulatory T cells, LAMP3+ tolerogenic dendritic cells, CCL18+ M2‐like macrophages, RGS5+ cancer‐associated fibroblasts, and LGALS1+ microglial cells. In addition, PD‐1 and PD‐L1/2 are barely expressed in CD8+ T cells and cancer/immune/stromal cells, respectively. Interactions of the immune checkpoint molecules LAG3‐LGALS3 and TIGIT‐NECTIN2 between CD8+ T cells and cancer/immune/stromal cells are found to play dominant roles in the immune escape. In summary, this study dissects the intratumoral heterogeneity and immunosuppressive microenvironment in liver and brain metastases of breast cancer for the first time, providing insights into the most appropriate immunotherapy strategies for these patients. Abstract : High‐resolution landscapes of the entire tumor ecosystem from breast cancer liver and brain metastases are first depicted using single‐cell RNA sequencing. The metastatic breast cancer microenvironment features remarkable intratumoral heterogeneity and abundant immunosuppressive cells. This study provides unique insights into the immunotherapeutic strategies most appropriate for patients with liver or brain metastatic breast cancer.